Alphabet school - Johnson, Stephen (New York Simon & Schuster Books for young readers, 2015)
Explore the alphabet in everyday objects found at school in this dazzling picture book. A classroom companion to celebrated artist Stephen Johnson's Caldecott Honor book Alphabet City, this alphabet book is a tour de force in the genre. There is much more to this book than meets the eye!
4 - 8 years
Keywords: Alphabet books; Juvenile works